Evaluation of the efficacy of sodium valproate in convulsive status epilepticus following to ischemic stroke - Ozdemir, Hasan Huseyin; Mungen, Bulent; Ilhan, Selcuk (Assoc Arquivos Neuro- Psiquiatria, 2015)
Objective: Convulsive status epilepticus (CSE) is very rarely observed after ischaemic stroke. Sodium valproate (SV) is one of the agents used in the treatment of CSE, but its role still controversial, and its degree of efficacy in treating CSE that develops following stroke is unclear. Method: We evaluated 19 patients who were treated with intravenous (IV) SV (20 mg/kg, 2 mg/kg/h-12h) after diazepam. Patients' modified Rankin scores (mRS), SE types, and changes in biochemical parameters after treatment were assessed. Results: CSE was successfully treated in 12 (63.15%) patients. Side effects such as hypotension and allergic reactions were observed in two patients. Refractory SE development was observed in 5 (29.4%) patients with high mRS (>3). No significant deterioration in patients' laboratory evaluations, conducted before and after status, was observed. Conclusion: SV may be safe and effective in the treatment of CSE observed after ischaemic stroke, especially in patients with low mRS.
Avaliação da eficácia do valproato de sódio no status epilepticus convulsivo devido ao acidente vascular cerebral isquêmico
Keywords: convulsive status epilepticus; ischaemic stroke; sodium valproate